Public Policy and the Enviroment : Survey of the Literature. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper notes that market failure, policy failures, and population pressures are major sources of environmental degradation and that linkages between economic activities and the environment exist at the levels of macroeconomic objectives, macroeconomic policy instruments, implementation of environmental policies, and measurement of economic activity. This paper also points out that fiscal instruments can, and indeed do, play a significant role in resolving environmental problems. In addition, market-based solutions, including pollution permits, also have merit. This paper further points out that implementing environmental policies poses considerable challenges for public policymakers and concludes by suggesting areas for further research.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet